Keterkaitan Antar Bursa Efek Dunia (Studi Kasus pada Bursa Efek Negara Maju dan Negara Berkembang) - Muhammad Madyan; Haka Adila; Novian Abdi Firdausi (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2019)
This research analyzes the correlation between stock markets worldwide. Developing countries stock exchanges are represented by China and Indonesia, whereas developed countries stock exchanges are represented by Germany, Japan, Australia, Singapore, and the United States. Using stock’s daily close prices as data, then assessed with Vector Error Correction Model and Granger Causality. Analyzed indexes are Shanghai Stock Exchange Composite (SHCOMP), Indeks Harga Saham Gabungan (IHSG), Dow Jones Industrial Average (DJIA), Nikkei225 (NKY), Deutscher Aktien Index (DAX), All Ordinaries Index (AOI), and Strait Times Index (STI). Stock data grouped into two periods, the first period is the Asian Financial Crisis in 1 January 1998-31 December 2003, while second period is the Subprime Mortgage crisis in 1 January 2008-31 December 2013. Research results show correlations between analyzed stock indexes in both long run and short run relationship in the firstperiod as well asthe second period, however the correlation between Singapore’s and Indonesia’s stock exchange in second period is unproven.